PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI MADRASAH ALIYAH ALKHAIRAAT FALABISAHAYA KABUPATEN KEPULAUAN SULA - Maani Pora (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The condition of parents' economic socialization in the sub-district village is still low. It can be seen that most parents whose profession is fishermen are then used as one of the livelihoods to support the economy and can also continue their children at the level of education whose income is below average. In terms of student motivation in villages around Falabisahaya, it still looks low. This problem makes researchers interested in conducting research whose results can motivate some children to be able to continue their education. Children's learning motivation affects parents' income, because economic conditions are also an indicator to boost children's enthusiasm and desire to continue their education. The conclusion of this study is that socio-economic conditions greatly influence students' interest in learning, which in turn indirectly influences the progress of the quality of education.